Health-Promotion Approaches to Postpartum Hypertension: Systematic Review of Causes and Management in Maternal Health - Efri Leny Rauf; St. Maisuri T. Chalid; Irfan Idris; Suryani As’ad; Ira Jayanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Postpartum hypertension remains one of the leading causes of maternal morbidity and mortality worldwide. This condition may persist from gestational hypertension, preeclampsia, or chronic hypertension, and can also develop de novo postpartum. Understanding its etiology, risk factors, and management strategies is essential to improving maternal health outcomes and preventing long-term cardiovascular complications. Methods: This study applied a systematic review design based on the Arksey and O’Malley framework, guided by the PEOS (Population, Exposure, Outcome, Study Design) model. A comprehensive literature search was conducted across PubMed, ScienceDirect, EBSCO, and Google Scholar databases for studies published between 2009 and 2023 using the keywords “postpartum hypertension,” “causes,” and “management.” Out of 120 identified studies, 20 met the inclusion criteria and were critically appraised using the Hawker Quality Assessment tool. Results: Postpartum hypertension is most frequently associated with preeclampsia, chronic hypertension, and gestational hypertension; however, iatrogenic causes such as bromocriptine therapy and excessive sodium intake were also identified. Most women experience a transient rise in blood pressure within the first 5 days postpartum, attributed to increased intravascular volume. The majority of studies emphasized inadequate screening and follow-up during the first week after delivery, with up to one-third of patients remaining untreated. Recent interventions, including digital monitoring systems and eHealth-based self-management, demonstrated improved outcomes in detection and patient adherence. Conclusion: Effective management of postpartum hypertension requires timely diagnosis, structured follow-up, and coordinated transition to primary care for long-term cardiovascular risk reduction. Health-care providers must enhance awareness and clinical competence, as complications from misdiagnosis or undertreatment remain common yet preventable through integrated postpartum surveillance and health-promotion strategies.